የኢትዮጵያ ኦርቶዶክስ ተዋሕዶ ቤተክርስቲያን መንፈሳዊ ፍርድ ቤት መቋቋም አስፈላጊነትና ምቹ ሁኔታዎች: ሙሉጌታ ጌጡ ፣ በላይነው አሻግሬ እና ዓለማየሁ ይስማው (Journal-of-Ethiopian-Church-Studies/የኢትዮጵያ-ቤተ-ክርስቲያን-ጥናት-መጽሔት-Live, 2012)
In the early times, when the Orthodox Church was a state religion, the Ethiopian Orthodox Tewahido Church was able to extend its thoughts, values, cultures in all government affairs. Accordingly, the Church law, especially the Fetha Negest (The Law of Kings), became the governing law of the state since its introduction into Ethiopia; The judges have also been those who have knowledge of the Church dogmas, faith, orders, and values. In this early period, the church had its own adjudicative organ, the ecclesiastical court, which adjudicate disputes that pertain to church affairs. At present, due to the separation of state and religion, the Church suffered from an external pressure since the regular/government courts are unable to preserve its interest, peace, and age-old contribution. This resulted in a lack of just, fair and honest/integrity decision in a dispute between the Church and its workers, embarrassing its internal matters, adjudication of church disputes by judges who do not have knowledge of the church’s dogma, faith, orders, values. Some regular courts have decided that they do not have jurisdiction to entertain cases arising from the church, for example, employment disputes between the Church and its priests. Though the 1995 constitution of FDRE provides that a religious court will be established separate from the regular courts, the EOTC did not do much for the establishment of an ecclesiastical court. This article addresses issues concerning the ecclesiastical courts. Particularly, the article assesses the contribution of the establishment of an ecclesiastical court to the Church, for national interest, the existence, or otherwise, of a legal framework for its establishment.